The α-Gal mammalian meat allergy as a cause of isolated gastrointestinal symptoms - Richards, Nathan E.; Makin, Tom A.; Smith, Anna R.; Platts-Mills, Thomas A. E.; Richards, Robert D.; Wilson, Jeffrey M. (Frontiers in Gastroenterology, 2022)
The α-Gal mammalian meat allergy classically presents with urticaria, with or without gastrointestinal (GI) symptoms or anaphylaxis, but increasingly we are aware of patients with only GI symptoms. Here we describe patients presenting with isolated GI symptoms who had detectable IgE antibodies to α-Gal and reported symptom improvement on a mammal-restricted diet. Forty patients in the practice of a single gastroenterologist, and 35 patients in one allergy clinic were identified, with abdominal pain, diarrhea, and nausea the most common symptoms. Alpha-Gal IgE levels were lower than in a previously described cohort of patients who exhibited classic allergic reactions. This large case series suggests that α-Gal IgE is an important contributor to GI morbidity in areas where lone star tick bites are common. Symptom presentations in GI-AGS can be easily confused with other common GI conditions, and α-Gal IgE levels are often lower than those in patients with classic AGS.